From schadenfreude to mitfreude? Estimating viewership loss and rivalrous relationships in otherwise neutral markets. Issue 2 (April 2017) - Sung, Hojun; Mills, Brian M.; Tainsky, Scott
Highlights: We estimate NFL neutral market broadcast viewership loss during a rival team's game. Games featuring a market's rival retain viewers more than games not featuring a rival. Markets are more likely to stay tuned in games that the rival wins. Abstract: We measure the loss in viewership over the course of National Football League games to identify engagement of out-of-market viewers throughout the contest, and how this is moderated by the presence of a rival team in the game. Our analysis reveals that out-of-market viewers are more likely to stay tuned throughout a game when their local team's rival is ultimately the game winner. This brings about important considerations in the context of measuring the effect of rivalry on demand. Our results point toward future research within the context of in-group bias and mitfreude behaviors in rivalrous relationships such that viewership depends not only on home team and in-group competitiveness, but also highlights preferences such as out-group competitiveness, or lack thereof. We therefore suggest an amendment to the Neale and Rottenberg frameworks to include how rivalry induces competitive complementarity.